Proceedings of the 5th ACM International Conference on Collaboration Across Boundaries: Culture, Distance &Amp; Technology 2014
DOI: 10.1145/2631488.2631495
|View full text |Cite
|
Sign up to set email alerts
|

Do automated transcripts help non-native speakers catch up on missed conversation in audio conferences?

Abstract: Previous work has suggested that speeded up playback of recorded audio works well for native speakers (NS) to catch up on conversation they missed in real-time audio conferences. However, this might not be the case for nonnative speakers (NNS) who normally have lower listening ability in their second language. In this study, we explore whether automated speech recognition (ASR) technology can aid NNS when combined with speeded up audio playback. We conducted a laboratory experiment in which 18 NS and 18 NNS li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Significant previous work has focused on exploring tools to aid NNS in multiparty collaborations. The most widely adopted approach is to provide NNS with automated transcripts, which improves comprehension in audio and video meetings [53], and helps NNS catch up on missed conversation [31]. These approaches have both benefits and costs for NNS, because reading automated transcripts while following the ongoing conversation can create greater cognitive load.…”
Section: Challenges In Multiparty Communication Between Ns and Nnsmentioning
confidence: 99%
“…Significant previous work has focused on exploring tools to aid NNS in multiparty collaborations. The most widely adopted approach is to provide NNS with automated transcripts, which improves comprehension in audio and video meetings [53], and helps NNS catch up on missed conversation [31]. These approaches have both benefits and costs for NNS, because reading automated transcripts while following the ongoing conversation can create greater cognitive load.…”
Section: Challenges In Multiparty Communication Between Ns and Nnsmentioning
confidence: 99%
“…According to previous research, real-time transcripts generated by ASR technologies hold the potential to facilitate the listening comprehension of NNSs [4]. ASR transcripts provide textual information that can complement audio speech and improve the comprehension of NNSs [5], [9]. Pan et al investigated how the quality of ASR transcripts impact comprehension and found that a 20% word-error-rate (WER) was the critical point for transcripts to be acceptable, and at a 10% WER, comprehension performance significantly improved compared to a no-transcript condition [4].…”
Section: Supporting Nnss' Listening Comprehension With Asr Transcriptsmentioning
confidence: 99%